miR-34c-5p functions as pronociceptive microRNA in cancer pain by targeting Cav2.3 containing calcium channels - Gandla, Jagadeesh; Kuner, Rohini; Bali, Kiran Kumar (Pain, 2017)
Pathophysiological mechanisms underlying pain associated with cancer are poorly understood. microRNAs (miRNAs) are a class of noncoding RNAs with emerging functional importance in chronic pain. In a genome-wide screen for miRNAs regulated in dorsal root ganglia (DRG) neurons in a mouse model of bone metastatic pain, we identified miR-34c-5p as a functionally important pronociceptive miRNA. Despite these functional insights and therapeutic potential for miR-34c-5p, its molecular mechanism of action in peripheral sensory neurons remains unknown. Here, we report the identification and validation of key target transcripts of miRNA-34c-5p. In-depth bioinformatics analyses revealed Cav2.3, P2rx6, Oprd1, and Oprm1 as high confidence putative targets for miRNA-34c-5p. Of these, canonical and reciprocal regulation of miR-34c-5p and Cav2.3 was observed in cultured sensory neurons as well as in DRG in vivo in mice with cancer pain. Coexpression of miR-34c-5p and Cav2.3 was observed in peptidergic and nonpeptidergic nociceptors, and luciferase reporter assays confirmed functional binding of miR-34c-5p to the 3′ UTR of Cav2.3 transcripts. Importantly, knocking down the expression of Cav2.3 specifically in DRG neurons led to hypersensitivity in mice. In summary, these results show that Cav2.3 is a novel mechanistic target for a key pronociceptive miRNA, miR-34c-5p, in the context of cancer pain and indicate an antinociceptive role for Cav2.3 in peripheral sensory neurons. The current study facilitates a deeper understanding of molecular mechanisms underlying cancer pain and suggests a potential for novel therapeutic strategies targeting miR-34c-5p and Cav2.3 in cancer pain.